A equidade no acesso às universidades federais e a aplicação da ação afirmativa de regionalidade na ufersa - Silvino, Wendson Max (Universidade Federal Rural do Semi-Árido, 2018)
The current national education plan, in its goal 12, establishes higher rates of schooling, the gross rate to 50%, and the net rate to 33%, making Brazil switch from the elite education system to a mass system. To achieve the goal, the plan establishes strategies to reduce the inequalities of access of groups that have historically been deprived of this freedom, are the high school graduates of public schools, blacks, browns and indigenous people, low income people, and disabled people. The research analyzed the inclusion of these groups from the point of view of the equity suggested for them in the quota law. The bibliographical research was carried out on the themes of equity in the new public administration, equality and freedoms. Also on concepts of efficiency, efficacy and effectiveness in public policies. An abstract was made about the history, vacancies, forms of access, elitisation and affirmative actions in higher education in Brazil. In the exploratory research, the current target indexes and UFERSA collaboration were analyzed, for which the net rate of the participants was measured. A qualitative analysis of the equity of the actions of the law was made. At UFERSA, this analysis took place quantitatively by the scaling of participation rates of the groups' entrants. In the third part of the case study, it was simulated the application of a new affirmative action in the UFERSA, the regionality factor, and measures the regionality rates before and after the application. The analysis showed that Brazil is unlikely to reach the targets of goal 12 of the plan. Despite this, federal universities have collaborated positively through the quota law. The law is being efficacy, as it is enabling an increase in the admission of students from those of the proposed groups. However, selection needs to be more efficient in the sense of lowering implementation hurdles such as income data conference and school type. The law also needs to be more effective, improving race share verification, addressing regional differences in income share and differences between state and federal schools. The only action with potential to satisfy the equity of the proposed group effectively is the quota for the disabled, since it requires medical confirmation. The regionality action has been implemented by universities and has proved necessary, especially for elite courses such as medicine, to enable more candidates to join from the region. In UFERSA, this action would increase the regionality, as well as increase the net rate of the entrants
Keywords: Equidade; Lei das cotas; Ação afirmativa; Inclusão regional; Cesso à educação superior; Avaliação de política pública; Equity; Law of quotas; Affirmative action; Regional inclusion; Access to higher education; Public policy evaluation; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA